1991
DOI: 10.1007/bf00028735
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of tomato cDNA and genomic clones encoding the ubiquitin gene ubi3

Abstract: We report here the isolation and nucleotide sequence of tomato cDNA and genomic clones encoding a ubiquitin extension protein homologous to the yeast gene ubi3. Sites similar to upstream activating sites commonly found in the promoters of yeast ribosomal genes were observed in the tomato promoter. The tomato ubi3 promoter also contained elements found in the rbcS promoter from pea. The transcription initiation site was determined to occur 66 bp upstream of the initiating Met. RFLP mapping revealed that the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 36 publications
1
57
0
1
Order By: Relevance
“…Furthermore, and contrary to what happsns in some animal systems (Muller-Taubenberger et al, L989), plant extension proteins are rapidly cleaved to produce free ubiquitin (Callis et al, 1990). Their expressim patterns would also be different from that of UbiS "As, because extension proteins are usually expressed in higlily dividing cells and seldom up-regulated in response to stress (Callis et al, 1990;Hoffman et al, 1991). In contrast expression during the desiccation stages of embryogenesis of proteins in band IV (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, and contrary to what happsns in some animal systems (Muller-Taubenberger et al, L989), plant extension proteins are rapidly cleaved to produce free ubiquitin (Callis et al, 1990). Their expressim patterns would also be different from that of UbiS "As, because extension proteins are usually expressed in higlily dividing cells and seldom up-regulated in response to stress (Callis et al, 1990;Hoffman et al, 1991). In contrast expression during the desiccation stages of embryogenesis of proteins in band IV (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This, together with observation of differential regulation of severa1 plant ubiquitin genes, has suggested that their multiplicity and diversity reflect an evolutionary divergence of their gene regulation to cope with different specific tasks, such as functions related to cell proliferation and dedifferentiation (Gausing and Barkardottir, 1986;Jamet et al, 1990;Genschik et al, 1992); stress, light, or hormone responses (Burke et al, 1988;Binet et al, 1991;Hoffman et al, 1991;Garbarino et al, 1992;Genschik et al, 1992;Reynolds and Hooley, 1992); and organ (flower, leaf, etc.) development (Gausing and Barkardottir, 1986;Burke et al, 1988;Hoffman et al, 1991;Garbarino et al, 1992). The differential regulation of tetraubiquitin mRNAs during seed maturation and detection of putative, seed-specific, protein-ubiquitin conjugates reported in this study suggest that distinct ubiquitin genes could perform specific functions during plant zygotic embryogenesis.…”
mentioning
confidence: 99%
“…The qRT-PCR reaction was performed using miraculin-specific primers and ubiquitin3-specific primers. Ubiquitin3 has been described previously (Hoffman et al 1991) and was used as a control (Hackel et al 2006;Leclercq et al 2005). The primer sequences have also been described previously (Kim et al 2010).…”
mentioning
confidence: 99%
“…Expression of genes associated with phenylpropanoid and flavonoid biosynthesis was assessed using probes generously provided by Dr. Cathie Martin (John Innes Centre, Norwich, UK). A Datura stramonium ubiquitin sequence was generated by PCR from genomic DNA using primers derived from the tomato sequence (sense, 5Ј-ATGCAGATCTTCGTGAAAAC-3Ј; antisense, 5Ј-CTTAACCTTCTTCTTCTTCTGCTT-3Ј [Hoffman et al, 1991]). Tobacco ubiquitin and ␤-1,3-glucanase (PR2) coding sequences were amplified by PCR from tobacco genomic DNA using oligonucleotide primers derived from published sequences (ubiquitin sense, 5Ј-TGGCTCAGGATGAACGCTGGC-3Ј; antisense, 5Ј-CATCTT-TGAGACCTCAGTAGAC-3Ј [Karrer et al, 1998]; PR2 sense, 5Ј-CAT-GCAAACAATTTACCATCAGACC-3Ј; antisense, 5Ј-CCAGGTTTCTTT-GGAGTTCCTGCC-3Ј [Ward et al, 1991]).…”
Section: Molecular Analysis Of Plantsmentioning
confidence: 99%